Tensile, flow and thermal properties of biodegradable PLA/Kenaf fibre composite: article - Azri, Muhammad Ridhwan; Sharudin, Rahida Wati; Mohamed, Rahmah (2019)
This research was conducted to study the flow, chemical, mechanical and thermal properties of biodegradable PLA/Kenaf fibre composite. The PLA resin compounded with kenaf fibre via twin screw extruder with different composition of kenaf from the prepared formulation. The PLA composite of different kenaf composition was then tested for its flow, chemical, mechanical and thermal properties by using testing equipments such as Melt Flow Tester, FTIR, Tensile Tester and Differential Scanning Calorimetry (DSC).